Dinamika Epistemologi Studi Islam di Kalangan Insider dan Outsider - Zaini Tamin AR; Nia Indah Purnamasari (LPPM STAI Ihyaul Ulum Gresik, 2020)
Islam as a study is still an interesting discourse among scientists. Moreover, when associated with epistemological aspects that are always dynamic along with the development of approaches, disciplines and methodologies. Therefore, this library research seeks to analyze the epistemological dynamics of Islamic studies that go hand in hand with the struggles of Islam, society, and the challenges facing Muslims in actualizing their teachings. This study reveals the findings that in Islamic studies there are often differences in viewing normative and historical aspects. Both aspects, making Islamic studies seem to still be burdened by romantic and apologist religious missions. So the content of analysis, critical, methodological, historical, empirical, especially in examining religious texts or texts as historical products is less visible, except in certain research environments that are still very limited. As these academic trends became stronger, Islamic studies began to be elaborated with several more varied approaches and methods than ever before, ranging from humanities, theology, social sciences, and regional studies. This approach requires mastery of interdisciplinary and multidisciplinary science. In other words, inter and multidisciplinary are very important scientific tools to support the development of Islamic studies.